IMPACTS OF AGING ON THE MALE REPRODUCTIVE SYSTEM: HORMONAL, METABOLIC AND REPRODUCTIVE CHANGES - Melo de Andrade Rodrigues, Ana Clara; Carolina Ribeiro Dias, Fernanda; Moreira Gomes, Marcos de Lucca (Acta Biologica Brasiliensia, 2025)
Aging gradually affects the male genital system due to profound hormonal and metabolic changes. The reduction in the proportion of testicular blood vessels reduces the supply of oxygen and other nutrients to the organ’s parenchyma, increasing inflammatory conditions and oxidative stress, which can significantly affect sperm viability and morphology. Aging has an impact on lipid and protein metabolism, which can compromise sperm structure and functionality. In addition, sperm can accumulate significant changes in their DNA, increasing the chance of mutations with consequent harmful consequences for their offspring, such as autism spectrum disorders, schizophrenia, and attention deficit disorders. Therefore, understanding the male aging process and its consequences for men’s reproductive health is of utmost importance for the prevention and treatment of diseases related to the male genital tract.